Integrating Outcome-based Education Curriculum and Digital Citizenship to Strengthen Pancasila Values - Susi; Mohamed Shah bin Hussin Shah (Jurnal Kewarganegaraan, 2026)
Digital transformation and the development of Society 5.0 require higher education to produce graduates who are not only technically competent but also possess ethical awareness, social responsibility, and a strong sense of citizenship. In the Indonesian context, strengthening Pancasila values through digital citizenship represents a strategic agenda that must be systematically integrated into the curriculum. This study aims to synthesize Scopus-indexed scholarly literature examining the relationship between Outcome-Based Education (OBE), digital citizenship, and the strengthening of Pancasila values in higher education. A Systematic Literature Review (SLR) was conducted through identification, screening, and thematic analysis of 30 selected articles published between 2019 and 2025. The screening process applied inclusion–exclusion criteria and quality assessment to ensure methodological rigor. The findings indicate that OBE provides an effective structural framework for integrating digital citizenship as value-based learning outcomes; however, studies explicitly linking OBE to Pancasila values remain limited. This synthesis concludes that OBE can function as a strategic instrument for strengthening value-based digital citizenship and recommends curriculum development and further research to support its implementation in higher education.